Phosphate distribution in the sediments along a cascade of reservoirs - (Paranapanema River, SE, Brazil) - Jorcin, A.; Nogueira, M. G. (Backhuys Publishers, 2005)
Total phosphorus concentrations in the sediment of a cascade of 8 reservoirs located in the Paranapanema River (SE, Brazil) were analysed during two consecutive seasonal periods (2000 and 200 1). The reservoirs of Jurumirim, Chavantes, Salto Grande, Canoas 11, Canoas 1, Capivara, Taquarucu and Rosana were built during the last five decades with the purpose of hydroelectric generation. The sampling points were distributed along a 700 km of river stretch in 19 stations distributed in the river-reservoirs zones and main tributaries as well as in 5 stations representing the adjacent wetlands. The nutrient concentration was determined in samples from surface layers of sediment. Temporal and spatial changes were observed for both years. Three different areas could be identified along the river, considering not only Tot-P variations but also others physical and chemical characteristics such as organic matter concentration, nitrogen concentration of sediment and 02, pH, conductivity and Eh measured in the bottom layer of the water column. Higher values of Tot-P were found in the middle and lower region of the Paranapanema basin (maximum value of 1.96 mg g(-1) in Tibagi River in October/2001). Agricultural practices and cattle raising are the main external sources of nutrient in these regions. Superficial or sub-superficial watershed drainage and tributaries entrances are important nutrient contributors, leading to an increasing accumulation of nutrient in the sediment. This process seems to be especially important in the middle region of the Paranapanema Valley, were the values of Tot-P were higher comparing to the other areas.
Keywords: phosphate; sediment; cascade reservoirs; Brazil